1992
DOI: 10.1073/pnas.89.10.4412
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of nuclear compartmentalization of glutathione in hepatocytes.

Abstract: The intracellular distribution of glutathine (GSH) in cultured hepatocytes hasbeen investigated by using the compound monochlorobimane (BmCI) Approximately 10-20% of total cellular GSH in rat liver is sequestered in the mitochondrial matrix (6, 7). The size ofthis pool depends on cytosolic GSH synthesis (8) and the active transport of GSH into mitochondria via a multicomponent system recently described (9).Conventional cell-fractionation studies have not provided evidence for the existence of functionally dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
136
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(141 citation statements)
references
References 37 publications
3
136
1
Order By: Relevance
“…Although this mitochondrial GSH is sensitive to depletion by many antitumor agents, it is relatively insensitive to BSO depletion. Likewise, many reports have suggested that GSH pools in nuclei are more resistant than those in the cytoplasm to BSO depletion (42)(43)(44)(45)(46). However, since our knowledge is rather limited at this point, it is speculated that these compartmentalized GSH levels may play a dominant role in controlling intracellular ROIs and gene regulation compared with those in the cytoplasmic compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Although this mitochondrial GSH is sensitive to depletion by many antitumor agents, it is relatively insensitive to BSO depletion. Likewise, many reports have suggested that GSH pools in nuclei are more resistant than those in the cytoplasm to BSO depletion (42)(43)(44)(45)(46). However, since our knowledge is rather limited at this point, it is speculated that these compartmentalized GSH levels may play a dominant role in controlling intracellular ROIs and gene regulation compared with those in the cytoplasmic compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Before the toxic dose was given, the glutathione content in the liver of pretreated rats was reduced to 60% of that of the controls ( fig. 3A), indicating depletion of the cytosolic (extranuclear and -mitochondrial) pool (Bellomo et al 1992;Meredith & Reed 1982). This may be the result of either low synthesis rate or high consumption rate of glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, nuclear GSH has been shown to be rather resistant to depletion by, e.g. buthionine sulfoximine, N-ethylmaleimide, and maleate, respectively, in comparison to the cytoplasmic GSH, suggesting that nuclear GSH is important against oxidative damage of the nuclear DNA and nuclear proteins (64). Reactions between proteins and GSH or GSSG alone are rather slow and unspecific.…”
Section: Fig 6 Multiple Tissue Northern Blot Analysis Of Human Grx1mentioning
confidence: 99%